Modeling a storage tank of carbon capture technology in a power plant in southern Iraq - Mustafa M. Mansour; Alaa M. Lafta; Haider Sami Salman; Sarah R. Nashee; Ahmed J. Shkarah (BIORE Scientia Academy, 2024)
The IEA's special study on CO2 collection, usage, and storage, released in 2020, estimates global CO2 capacity for storage to be among 8,000 and 55,000 gigatons. One of the most significant issues in introducing carbon into the energy market is improving carbon storage and developing more efficient distribution systems to increase the quantity of carbon that is held as liquid while decreasing storage pressure. The goal of this work is to investigate the efficiency of adsorption-based carbon-storing units from a